A New Viscosity Equation For Bin Aqueous Solutions. - Tan, C. S.; Teng, T.T.; Hakimi, Mahamad; Lim, C. P.; Pang, F. M.; Seng, C. E. (2004)
An equation for the viscosity of binary aqueous solutions has been derived based on the Power law equation and Erying's absolute rate theory. The concentration dependent equation for viscosities of binary aqueous systems is derived using additive contribution from water and solute component. The equation has sufficient degree of freedom to represent the' whole range of concentration. The equation has been applied to 12 nonelectrolyte aqueous systems and 10 electrolyte systems at various temperatures. An average absolute deviation percentage error' (AAD%) of 0.2856% is reported for electrolyte systems: For non-electrolyte systems an average AAD% of 0.7843% is reported. Overall, the equation is found to have yielded an AAD% of 0.5576%.